2015
DOI: 10.1123/pes.2014-0074
|View full text |Cite
|
Sign up to set email alerts
|

Sedentary Time and Screen-Based Sedentary Behaviors of Children With a Chronic Disease

Abstract: The objectives of this study were to (i) assess sedentary time and prevalence of screen-based sedentary behaviors of children with a chronic disease and (ii) compare sedentary time and prevalence of screen-based sedentary behaviors to age- and sex-matched healthy controls. Sixty-five children (aged 6-18 years) with a chronic disease participated: survivors of a brain tumor, hemophilia, type 1 diabetes mellitus, juvenile idiopathic arthritis, cystic fibrosis, and Crohn's disease. Twenty-nine of these participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 0 publications
1
36
1
2
Order By: Relevance
“…22 Survivors spent more time per day in sedentary behavior than reported in the general population (66% vs 60%, respectively), 6 but less than that reported by Walker et al among young children/adolescents with chronic diseases, including survivors of brain tumors (66% vs 77%, respectively). 23 In contrast to the results of the current study, Walker et al found no differences between survivors and controls; however, the comparison sample size was small (29 participants), heterogeneous in terms of disease, and based on a much younger population. Increased screen time and sedentary behavior were found to be associated with a lower percentage lean mass, with a similar association described in communitydwelling older adults.…”
Section: Discussioncontrasting
confidence: 99%
“…22 Survivors spent more time per day in sedentary behavior than reported in the general population (66% vs 60%, respectively), 6 but less than that reported by Walker et al among young children/adolescents with chronic diseases, including survivors of brain tumors (66% vs 77%, respectively). 23 In contrast to the results of the current study, Walker et al found no differences between survivors and controls; however, the comparison sample size was small (29 participants), heterogeneous in terms of disease, and based on a much younger population. Increased screen time and sedentary behavior were found to be associated with a lower percentage lean mass, with a similar association described in communitydwelling older adults.…”
Section: Discussioncontrasting
confidence: 99%
“…This suggests that epigenetic repression of the C9ORF72 promoter leading to reduced transcription and DPR production likely accounts for the reduced levels of DNA DSB markers in C9ALS-2 iMNs. Epigenetic repression of the C9ORF72 locus has been shown to alter C9ORF72 RNA splicing, DPR production and features of the C9ALS/FTD clinical presentation [60][61][62]. While based on only two cell lines, our results suggest C9ORF72 promoter hypermethylation alters DNA damage phenotypes in C9ALS iPSC neurons as well.…”
Section: Dna Dsb Repair Proteins Are Elevated In C9als Ipsc Neurons Bmentioning
confidence: 55%
“…Five studies reported on accelerometers; 4 only included children, one only adults . One study explicitly aimed to validate an accelerometer (Actiheart, uniaxial accelerometer combined with heartrate) for the measurement of energy expenditure in children with different chronic diseases.…”
Section: Resultsmentioning
confidence: 99%